PENGEMBANGAN MEDIA PEMBELAJARAN PUZZLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA DI KELAS V SDN SERTAJAYA 05 - Neng Ernawati; Misbah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Low student learning outcomes can occur due to a lack of learning media used to facilitate students in learning. This research aims to develop puzzle media to improve the learning outcomes of elementary school students in class V. The research used is Research and Development (R&D). The results show that the puzzle media was declared